Determination of the reasons for the rupture of links in the product “round flat‑link chain” after mechanical tests for fatigue strength at the consumer - I. A. Kovaleva; N. A. Hodosovskaya; I. A. Guzova (Литьë и металлургия)
The article describes the conducted research of the product “round flat‑link chain”, with the rupture of three links after heat treatment and mechanical tests at the consumer. The purpose of the research was to determine the cause of the destruction of the chain links. Visual inspection of the chain revealed breaks in three of the nine links. The rupture occurred in the area of factory branding. A metallographic study of two samples cut from a chain link with a break and a link without a break was carried out. During the study, a surface layer was found that was distinguishable from the main microstructure. The presence of the detected surface layer is due to surface hardening. The hardened area of the surface of the link with a break is almost two times smaller than in the link without a break. The amount of residual austenite is larger and larger in the link with the gap. As a result of the conducted studies, it was found that the destruction of the chain links occurred due to a violation of the heat treatment regime of the surface layer.